Beggars, iconoclasts, and civic patriots : the political culture of the Dutch Revolt - Arnade, Peter J. (Cornell paperbacks., 2008)
The Dutch Revolt has long been hailed as the triumph of political freedom over monarchical tyranny. In 1781, John Adams observed that the American Revolution was its "transcript." Known for its many protagonists-King Philip II, the Duke of Alba, the counts of Egmont and Hornes, radical Calvinists, obstreperous townspeople, and William of Orange-the Dutch Revolt brought into relief conflicts among civic freedoms, religious dissent, representative institutions, and royal authority. Drawing on a vast array of sources-including archival documents, political and religious pamphlets, ballads, chronicles and letters, and a rich store of popular prints-Peter Arnade gives us a new history of the core years of the revolt between 1566 and 1585, showing how the act of rebellion forged a political identity through ritual, symbol, and public action. In Beggars, Iconoclasts, and Civic Patriots, Arnade focuses on the political culture that took shape during the Revolt, a culture that itself fueled decades of turmoil. He sees the pulse of the Revolt in its public dramatization-the acts, words, and cultural representations that were its "daily bread and popular voice."The violent wave of radical iconoclasm that swept the southern Netherlands in 1566 is the book's pivot, setting the stage for the Duke of Alba's brutal effort to restore the authority of the Spanish crown. Arnade details the sieges and violent sacks of Dutch cities by the Army of Flanders, and the response of Dutch rebels, who touted defiant cities as the seats and guarantors of unassailable rights and freedoms. This civic patriotism hailed William of Orange as father of the fatherland, his apotheosis hearkening back to late medieval princely ritual even as it invoked new republican imagery